2021
DOI: 10.2147/jir.s288280
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinases in Inflammatory Bowel Diseases

Abstract: Inflammatory bowel diseases (IBD) are chronic inflammatory diseases of the gastrointestinal tract, encompassing two main disorders: Crohn's disease (CD) and ulcerative colitis (UC). In both these pathologies, excessive and local immune response against luminal antigens promotes a pathological process leading to various degrees of gut damage. Matrix metalloproteinases (MMPs) are a family of neutral proteases with the ability to degrade all components of extracellular matrix. In physiological conditions, MMPs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 67 publications
2
33
0
Order By: Relevance
“…We further found that IL-26 can promote the mRNA and protein expression of MMP-8 and MMP-9 while inhibiting the expression of MMP-1 ( Figure 6 ). The overexpression of MMP-1, MMP-8, and MMP-9 is observed in the intestinal mucosa of IBD patients ( 48 ). MMP-9 has been implicated in the breakdown of intestinal epithelial barriers, and infiltrating macrophages are its primary producers in IBD ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…We further found that IL-26 can promote the mRNA and protein expression of MMP-8 and MMP-9 while inhibiting the expression of MMP-1 ( Figure 6 ). The overexpression of MMP-1, MMP-8, and MMP-9 is observed in the intestinal mucosa of IBD patients ( 48 ). MMP-9 has been implicated in the breakdown of intestinal epithelial barriers, and infiltrating macrophages are its primary producers in IBD ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of inflammatory proteases are elevated in the inflamed mucosa of IBD patients 37 . In particular, activated matrix metalloproteinases (MMPs), such as MMP3 and MMP12 are abundant in these tissues 38,39 . These MMPs exhibit proteolytic activity on a broad range of protein substrates, including native IgG, therapeutic monoclonal antibodies and biologics that contain a human Fc scaffold, such as the TNFα inhibitor etanercept 35 .…”
Section: Resultsmentioning
confidence: 99%
“…MMPs are produced in excess in inflamed intestinal tissues of IBD patients and causes mucosal degradation ( 33 ). Recent study showed that MMP12 mediated the degradation of basement membrane laminin and the transmigration across intestinal epithelial tight junctions of macrophages, and increased severity of DSS-induced colitis of mice ( 34 ).…”
Section: Discussionmentioning
confidence: 99%